Nonparameningeal alveolar rhabdomyosarcoma, with cytohistological features: A case report - Neelam Sood; Arun K Haldia (Wolters Kluwer Medknow Publications, 2019)
Rhabdomyosarcoma (RMS) is a tumor arising from primitive mesenchymal cell with tendency for myogenesis. WHO classification categorizes this entity as embryonal, alveolar, spindle cell/sclerosing, and pleomorphic subtypes removing botryoid as a separate entity. The alveolar variant has worse prognosis and the cytological features of this entity are similar to embryonal type with little variations. This case report describes the cytohistological features of alveolar RMSfrom a 9-year-old child with nonparameningeal location.